Relational Identity in Myrna Casas' El gran circo EUkraniano - Vargas, Margarita (Latin American Theatre Review, 2003)
This article examines characterization as well as the dramatic strategies and theatrical techniques used in the play to draw attention to the invisible bridge between fiction and reality in which Casas locates the elusiveness of both individual and national identity. By accentuating the fluidity of fiction and reality, Casas insinuates that it is no longer necessary to choose a fixed or stable identity, because the identity of a nation and that of its citizens continually adjusts to the political times and the social circumstances. In the case of Puerto Rico, instead of searching for a single authentic identity either in a Spanish past or in the current North American influence, there is a call for accepting change critically. (MV)